BOOK REVIEWS (Journal of Finance, 1963)
Book reviewed in this article: Business Finance: Corporate Finance—Policy and Management . By E lvin F. D onaldson and J ohn K. P fahl . Techniques of Financial Analysis . By E rich A. H elfert . Financial Management of the Marketing Function . By M ichael S chiff and M artin M ellman . Capital in the American Economy: Its Formation and Financing . By S imon K uznets . Optimal Investment Decisions: Rules for Action and Criteria for Choice . By P ierre M assé . Consumer Finance: Retail Credit Fundamentals , By C lyde W illiam P helps . International Finance: Studies in United States Commercial Policy . Edited by W illiam B. K elly , J r . Problems of the United States as World Trader and Banker . By H al B. L ary . International Finance—Theory, Practice, Institutions . By M ax J. W asserman , C harles W. H ultman , and L aszlo Z soldos . Investments: Trends in the Distribution of Stock Ownership . By E dwin B. C ox . Security Analysis: Principles and Technique . By B enjamin G raham , D avid L. D odd , and S idney C ottle , with the collaboration of C harles T atham . Money and Banking*: Savings Accounts and Commercial Bank Earnings . By A llan R. D rebin . Clarification of the Monetary Standard . By W ill E. M ason . Free Reserves and the Money Supply . By J ames A. M eigs . Financing American Enterprise—the Story of Commercial Banking . By P aul B. T rescott . Financial History of the United States . By P aul S tudenski and H erman E. K rooss . Real Estate Finance: Changing Urban Land Uses as Affected by Taxation . By J erome P. P ickard . The Valuation of Real Estate . By A lfred A. R ing . Related Disciplines: Invisible Barrier—the Optimum Growth Curve . By G eorge T. A ltman .